Inversion effects in the perception of the moving human form - A comparison of adolescents with autism spectrum disorder and typically developing adolescents - FITZGERALD, MICHAEL (My University, 2013)
The “body inversion effect” refers to superior recognition of upright than inverted images of the human body and indicates typical configural processing. Previous research by Reed et al. using static images of the human body shows that people with autism fail to demonstrate this effect. Using a novel task in which adults, adolescents with autism, and typically developing adolescents judged whether walking stick figures—created from biological motion recordings and shown at seven orientations between 0° and 180°—were normal or distorted, this study shows clear effects of stimulus inversion. Reaction times and “inverse efficiency” increased with orientation for normal but not distorted walkers, and sensitivity declined with rotation from upright for all groups. Notably, the effect of stimulus inversion was equally detrimental to both groups of adolescents suggesting intact configural processing of the body in motion in autism spectrum disorder.
PUBLISHED
PMID: 24126867 ABSTRACT:The "body inversion effect" refers to superior recognition of upright than inverted images of the human body and indicates typical configural processing. Previous research by Reed et al. using static images of the human body shows that people with autism fail to demonstrate this effect. Using a novel task in which adults, adolescents with autism, and typically developing adolescents judged whether walking stick figures-created from biological motion recordings and shown at seven orientations between 0° and 180°-were normal or distorted, this study shows clear effects of stimulus inversion. Reaction times and "inverse efficiency" increased with orientation for normal but not distorted walkers, and sensitivity declined with rotation from upright for all groups. Notably, the effect of stimulus inversion was equally detrimental to both groups of adolescents suggesting intact configural processing of the body in motion in autism spectrum disorder
Keywords: Autism Spectrum Disorder; Neuroscience; AUTISM; AUTISM SPECTRUM; Adolescent Psychiatry; Autism; Autism; Autism; Autism; Autism; Autism Genetics; CHILD PSYCHIATRY; COMMUNITY PSYCHIATRY; CONSULTATION LIAISON PSYCHIATRY; CONSULTATION-LIAISON PSYCHIATRY; GENERAL HOSPITAL PSYCHIATRY; INFANTILE-AUTISM; INVERSION; INVERSIONS; LIAISON PSYCHIATRY; Neuropsychiatry; Neuropsychiatry; PERCEPTION; PERCEPTIONS; PSYCHIATRY; Perception; Philosophy of Psychiatry; Psychiatry; Psychiatry; SHAPE PERCEPTION; TRAINEES IN PSYCHIATRY; child and adolescent Psychiatry; forensic psychiatry; neurodevelopmental psychiatry; psychiatry services